2015
DOI: 10.1103/physreva.92.033613
|View full text |Cite
|
Sign up to set email alerts
|

Periodic shedding of vortex dipoles from a moving penetrable obstacle in a Bose-Einstein condensate

Abstract: We investigate vortex shedding from a moving penetrable obstacle in a highly oblate Bose-Einstein condensate. The penetrable obstacle is formed by a repulsive Gaussian laser beam that has the potential barrier height lower than the chemical potential of the condensate. The moving obstacle periodically generates vortex dipoles and the vortex shedding frequency fv linearly increases with the obstacle velocity v as fv = a(v − vc), where vc is a critical velocity. Based on periodic shedding behavior, we demonstrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 48 publications
4
69
1
1
Order By: Relevance
“…• Motion of a localized obstacle or potential (as generated by a tightly-focussed blue-detuned laser beam) through a condensate (or, equivalently, motion of the condensate relative to a static obstacle) leads to the nucleation of vortices above a critical relative speed [37,38,142], forming a quantum wake downstream of the obstacle. The critical speed is related to the Landau criterion which predicts the formation of elementary excitations in the fluid for relative speeds exceeding…”
Section: Summary Of Vortex Generation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Motion of a localized obstacle or potential (as generated by a tightly-focussed blue-detuned laser beam) through a condensate (or, equivalently, motion of the condensate relative to a static obstacle) leads to the nucleation of vortices above a critical relative speed [37,38,142], forming a quantum wake downstream of the obstacle. The critical speed is related to the Landau criterion which predicts the formation of elementary excitations in the fluid for relative speeds exceeding…”
Section: Summary Of Vortex Generation Methodsmentioning
confidence: 99%
“…(38) Substituting into the dipolar GPE (5) an equation for the amplitude f about the vortex is obtained,…”
Section: Energetics Of Vortex Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Would the superfluid show universal behavior in the wake response to a moving obstacle, and can we define a proper Reynolds number Re s characterizing it [2][3][4][5]? It has been clearly demonstrated that a superfluid becomes dissipative via quantum vortex emission when the obstacle velocity exceeds a critical velocity v c [6][7][8][9][10][11][12][13]. Since turbulent flow would be generated by strong perturbations of the obstacle at significantly high v, the key issue is whether regular vortex shedding like the von Kármán street occurs in an intermediate v regime.…”
mentioning
confidence: 99%
“…[11][12][13]. We prepare a highly oblate BEC of 23 Na atoms in a harmonic trapping potential which is generated by combining a pancake-shaped optical dipole trap and a magnetic quadruple trap.…”
mentioning
confidence: 99%